Vienne la Rouge - Werner Michael Schwarz; Georg Spitaler; Elke Wikidal (Cahiers d’histoire)
The coordinating curators of “Red Vienna 1919-1934”, an anniversary exhibition that was shown at Vienna’s Wien Museum MUSA in 2019, reflect on the conception and presentation of their exhibit about Vienna’s “communal socialism”, which flourished from the first free city council elections in 1919 until the violent destruction of democracy in Austria in 1933-34. Following a short history of the reception of previous exhibitions about Red Vienna, they advocate for the rediscovery of this era – in Austria and beyond – as a space of possibilities, a past future of a project committed to political emancipation that can also inform current debates on democratic participation and communal public spirit.